Quality of Service for Family Cards and Identity Cards in the Seduri Village Government, Balongbendo District, Sidoarjo Regency - Afinda Siti Fatimah; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2021)
There are violations in the main affairs of the population, such as the making of KK and KTP, making the service system weak. Whereas in providing service oriented to satisfaction. For example in the Seduri Village Government. Often village government officials make promises that are not realized. This causes the lack of clarity of time in providing services. This study aims to describe KK and KTP services in Seduri Village. The method used in this research is descriptive qualitative because the researcher wants to know and make a description or description in a systematic, factual, and accurate way about an object, a condition in the present and the relationship between the phenomena being investigated. The results of the study indicate that there are several constraining factors that make them unsatisfied in providing Family Card and Identity Card services such as clarity of time, delays in staff, and cost transparency.